Quenching of CdSe quantum dot emission, a new approach for biosensing. - Dyadyusha, L; Yin, H; Jaiswal, S; Brown, T; Baumberg, J; Booy, F; Melvin, T (2005)
The emission of CdSe quantum dots linked to the 5'-end of a DNA sequence is efficiently quenched by hybridisation with a complementary DNA strand with a gold nanoparticle attached at the 3'-end; contact of the quantum dot and gold nanoparticle occurs.